A Snapshot of a Coral “Holobiont”: A Transcriptome Assembly of the Scleractinian Coral, Porites, Captures a Wide Variety of Genes from Both the Host and Symbiotic Zooxanthellae - Shinzato, Chuya (Public Library of Science, 2014)
Massive scleractinian corals of the genus Porites are important reef builders in the Indo-Pacific, and they are more resistant to thermal stress than other stony corals, such as the genus Acropora. Because coral health and survival largely depend on the interaction between a coral host and its symbionts, it is important to understand the molecular interactions of an entire “coral holobiont”. We simultaneously sequenced transcriptomes of Porites australiensis and its symbionts using the Illumina Hiseq2000 platform. We obtained 14.3 Gbp of sequencing data and assembled it into 74,997 contigs (average: 1,263 bp, N50 size: 2,037 bp). We successfully distinguished contigs originating from the host (Porites) and the symbiont (Symbiodinium) by aligning nucleotide sequences with the decoded Acropora digitifera and Symbiodinium minutum genomes. In contrast to previous coral transcriptome studies, at least 35% of the sequences were found to have originated from the symbionts, indicating that it is possible to analyze both host and symbiont transcriptomes simultaneously. Conserved protein domain and KEGG analyses showed that the dataset contains broad gene repertoires of both Porites and Symbiodinium. Effective utilization of sequence reads revealed that the polymorphism rate in P. australiensis is 1.0% and identified the major symbiotic Symbiodinium as Type C15. Analyses of amino acid biosynthetic pathways suggested that this Porites holobiont is probably able to synthesize most of the common amino acids and that Symbiodinium is potentially able to provide essential amino acids to its host. We believe this to be the first molecular evidence of complementarity in amino acid metabolism between coral hosts and their symbionts. We successfully assembled genes originating from both the host coral and the symbiotic Symbiodinium to create a snapshot of the coral holobiont transcriptome. This dataset will facilitate a deeper understanding of molecular mechanisms of coral symbioses and stress responses.